Determinants of child nutritional status in the eastern province of Zambia: the role of improved maize varieties - Manda, J.; Gardebroek, C.; Khonje, M.G.; Alene, A.; Mutenje, M.; Kassie, M. (Springer, 2016)
Using household survey data from a sample of 810 households, this paper analyses the determinants of children’s nutritional status and evaluates the impacts of improved maize varieties on child malnutrition in eastern Zambia. The paper uses an endogenous switching regression technique, combined with propensity score matching, to assess the determinants of child malnutrition and impacts of improved maize varieties on nutritional status. The study finds that child nutrition worsens with the age of the child and improves with education of household head and female household members, number of adult females in the household, and access to better sanitation. The study also finds a robust and significant impact of improved maize varieties on child malnutrition. The empirical results indicate that adoption of improved maize varieties reduces the probability of stunting by an average of about 26%.